Dr. Michael M. Kim — Deep Plane Facelift — Portland - Kim, Michael M. (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Michael M. Kim, practicing in Portland, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003061; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; portland